1995
DOI: 10.1159/000282736
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Human Renal Cell Carcinoma with High-Energy Shock Waves–A New in vivo/in vitro Model

Abstract: The effects of high-energy shock waves (HESW) on the human renal cell carcinoma were examined. The kidneys were available from 32 patients treated by radical nephrectomy due to renal cell carcinoma. Immediately after nephrectomy the kidneys were perfused with cold HTK solution and stored for a maximum of 4h in hypothermia at 8°C. The tumors were treated with 4,000 shocks (65 mPa = 0.6 mJ/mm2) in an electromagnetic lithotriptor (Siemens Co., Erlangen, Germany). Microscopic and immunohistological exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the past, many studies of HESW were conducted on different human and animal tumour cell lines, describing an alteration of the cell growth (7)(8)(9)(10)(11). The in vitro effects of shock waves are due to a suppression of cell proliferation correlated with an apoptotic cell death process; moreover, HESW treatment has been shown to cause a transient increase in cell membrane permeability by opening micropores (such as electroporation), allowing higher intracellular drug concentration (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, many studies of HESW were conducted on different human and animal tumour cell lines, describing an alteration of the cell growth (7)(8)(9)(10)(11). The in vitro effects of shock waves are due to a suppression of cell proliferation correlated with an apoptotic cell death process; moreover, HESW treatment has been shown to cause a transient increase in cell membrane permeability by opening micropores (such as electroporation), allowing higher intracellular drug concentration (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The apparent feasibility of exposing a spatially limited region of the body to a potentially destructive form of mechanical energy has led to the idea of applying shock waves in tumor therapy. 4) Previous results have not necessarily been promising, in cases of shock wave therapy alone, [4][5][6][7][8] or in combination with various anti-cancer agents, for example, cisplatinum, [9][10][11][12][13] mitomycin C (MMC), 12,13) actinomycin D, 12) methotrexete 13) and adriamycin (ADR). 11,13,14) However, we have reported that the combination of focused shock waves and bleomycin (BLM) reduced the IC 50 of BLM to 1/10 000-1/100 000 in various human cancer cell lines, when compared to BLM alone.…”
mentioning
confidence: 99%